Understanding change blindness : current explanations and theories. - Tok, Yanshuang. (2012)
Change blindness is an interesting phenomenon in which people fail to see large observable and obvious changes that would normally be detected without difficulty. The various explanations proposed to explain the phenomenon can be classified under two classes, representation failures and non-representation failures. To date, however, there is no single theory able to fully account for the phenomenon of change blindness. Many theories extend their findings and complement one other. Some implications discussed in this review include individual differences in experiencing change blindness as well as humans’ overconfidence with their change detection ability. There remains potential for advancements in the field of change blindness.